PENGARUH MODEL LEARNING CYCLE 7E TERHADAP KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Ahmad Ibnu Rusydi; Hikmawati Hikmawati; Kosim Kosim (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2018)
This study aims to determine the effect of learning cycle model 7E on critical thinking skills of students of SMAN 1 Gerung. The research type is quasi experimental with post-test only control group design. Population is all class X MIPA SMAN 1 Gerung, with sampling technique using purposive sampling and obtained class X MIPA 3 as experiment class and class X MIPA 4 as control class. Data collection of critical thinking ability using the test technique in the form of a description of 5 questions that have been validated and reliable. Based on the result of research, it is found that the average post-test of critical thinking ability of experimental class is 66,02 and control class is 52,80. The obtained data were first tested for normality and homogeneity. Both classes were normally distributed and homogeneous, followed by hypothesis testing using statistical test (t-test polled variance). Test the hypothesis of critical thinking ability obtained t count value of 4,0928 and t table of 1.99656 at a significant level of 0.05, because t count is greater than t table, then H0 rejected and Ha accepted. The conclusion of this research is there is influence of learning cycle model 7E to critical thinking ability of students of SMAN 1 Gerung.